A framework of quality management practices for Indian service SMEs. Issue 1 (2nd January 2020) - Basu, Rana; Bhola, Prabha; Das, Manik Chandra
Abstract: This study adopts two-stage methodology by capturing the present implementation level of quality management (QM) practices and developed a framework as suggestive ranking by deploying fuzzy AHP and fuzzy TOPSIS to prioritize QM practices in context to Indian service SMEs with specific relevance to IT enabled enterprises. Suggestive ranking emphasize on practices like strategic issues, management focus, customer focus, human resource and process management for their survival in complex uncertain environment. The findings stated in this study are expected to offer practical guidelines to devise implementation strategies in order to precisely identify areas of concern and take corrective and preventive measures for quality improvement.